Improving solubility and storage stability of rifaximin via solid-state solvation with Transcutol®. Issue 35 (8th August 2019) - Grepioni, F.; Braga, D.; Chelazzi, L.; Shemchuk, O.; Maffei, P.; Sforzini, A.; Viscomi, G. C.
Abstract : Crystallization of rifaximin from Transcutol® affords the new anhydrous τ-form, which combines a high dissolution rate with a high storage stability, as it is not affected by exposure to humidity. Abstract : Crystallization of rifaximin from 2-(2-ethoxyethoxy)ethanol (Transcutol®, DEGME or DEGEE), an inactive ingredient approved by the FDA and a solvent commonly used in the pharmaceutical and cosmetic fields, affords a crystalline form of the API with better solubility properties with respect to the known crystalline hydrates, which are characterized by a very low solubility in water and in buffered solutions. The new form, namedrifaximin τ, is an anhydrous solvate, fully characterized by single crystal X-ray diffraction, differential scanning calorimetry (DSC) and thermogravimetric analysis (TGA). Solubility properties were also investigated and compared with known forms of rifaximin.Rifaximin τ combines a high dissolution rate, comparable to that of amorphous rifaximin, with a high storage stability, as in its solid form it is not affected by exposure to humidity.